Evaluation of the management and final disposal of the poultry litter of heavy breeders used as organic fertilizer in Costa Rica - Arce-Solano, Olga (2020)
Five poultry companies raise broiler breeders in Costa Rica. These birds go through two stages, rearing and laying, and at the end of each stage they generate the residue known as manure or litter. This study includes information from the five production companies supplemented with import data obtained from the National Animal Health Service (SENASA), in order to determine that the manure of broiler breeders in Costa Rica amounted more than 20 thousand metric tonnes of litter were produced in 2016. After a heating process on the chicken house, litter material goes out to a warehouse or passes directly to farms for it to be used in crops as fertilizer. During the research of the residue flow, the determination and evaluation of Critical Points (CP) were obtained, which resulted from deviations considered in the environmental effects, such as the use of poultry in agricultural soils in which the material is exposed to the environment or slightly covered with soil but after some days is uncover. When calculating the agricultural area that uses poultry manure, it was estimated that 2.404 hectares used this product in 2016, and if the growth rate of the population of broiler breeders is maintained, this area will be doubled within the next 20 years.